Sudden Cardiac Death - Magnusson, Peter; Ann LeQuang, Jo (IntechOpen, 2020)
Sudden cardiac death is a global health threat for which we have only partial answers. With growing elucidation of the underlying pathophysiological mechanisms of sudden cardiac death, better patient identification and treatment options are being developed. These include risk stratification paradigms, ICD therapy, pharmacological options, ablative procedures, and other treatments. This book covers many of these options, including defibrillator technology and clinical applications. It also examines pathophysiological pathways and etiologies as well as highlights risk-stratification in ion channel diseases and structural heart disease such as dilated cardiomyopathy.